PEMBUATAN SALUANG DAREK VERSI SABAR St MAHAJO KAYO SENIMAN TRADISIONAL DI NAGARI SINGGALANG DAN VERSI ZAINUDDIN SENIMAN AKADEMIS DI NAGARI KAYU TANAM (Studi Komparatif Dari Sudut Tinjauan Organologis) - Arifin Bahri; Wimbrayardi Wimbrayardi; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2012)
This study aims to (1) determine the manufacture of musical instruments saluang darek of two versions, version and version Zainuddin Tolerance through comparative studies of angle organologis review. (2) This research is a qualitative study using descriptive analysis. Data was collected through literature study, observation, interviews, photo shoots. (3) The results of the study is the comparison of instrument manufacture Saluang Darek Version Sabarudin St Mahajo Kayo Traditional Artist in Nagari Singgalang and Zainuddin Version Academic Artists in Nagari Wood Plant. how the process of making, playing techniques, tone and function dihasilakan instrument. Keywords: Making, Saluang, Comparative, Version, Nada.